2017
DOI: 10.1002/rcm.7931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relative electron ionization cross‐sections for some oxides and oxyacid salts

Abstract: The enthalpies of formation of gaseous cerium molybdates and tungstates were evaluated by measurements of the reaction enthalpies for several independent reactions. The best agreement was obtained with the data from the analysis of experimentally determined relative ionization cross-sections, and using ionization cross-sections of polyatomic molecules recommended by Drowart et al. The widely used additivity method, in spite of the additional corrections introduced, gives the worst convergence of the values und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The enthalpies of reactions 4–6 obtained by the 3 rd law (Equation ) and using the cross‐sections of reagents calculated by the additivity rule coincide within 3–4 kJ with the values obtained using the cross‐sections calculated according to the literature . Table S1 (supporting information) summarizes the data obtained using recommendations given in these citations …”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…The enthalpies of reactions 4–6 obtained by the 3 rd law (Equation ) and using the cross‐sections of reagents calculated by the additivity rule coincide within 3–4 kJ with the values obtained using the cross‐sections calculated according to the literature . Table S1 (supporting information) summarizes the data obtained using recommendations given in these citations …”
Section: Resultssupporting
confidence: 60%
“…In particular, the analysis of the experimentally obtained cross‐sections revealed that σ(MO)/σ(M) = 0.65, and σ(M 2 O 2 )/σ (MO) = 1.25. For the cross‐sections of oxy‐acid salts we proposed using the sum of the cross‐sections of the oxides forming the salt, multiplied by 0.7 . The ionization cross‐sections ( σ i ) and the secondary electron multiplier gain factors (γ i ) for the gaseous species in the vapor over the BaO–SnO 2 system are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations